Initial radiological signs of dentofacial deformity in juvenile idiopathic arthritis - Peter Stoustrup (Nature Portfolio, 2021)
Abstract Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in childhood and the temporomandibular joint (TMJ) is often involved. TMJ arthritis in growing individuals can cause deformation of facial skeleton (dentofacial deformity) and TMJ components (TMJ deformity). Treatment outcome hinges on early initiation of anti-inflammatory treatment and orthopaedic treatment with dental splints. The aim of the present study was to characterize the radiological signs of dentofacial deformity in patients with a JIA-induced need for orthopaedic treatment. We retrospectively studied 96 patients with JIA and 20 non-JIA controls to identify the initial radiological signs of JIA-induced dentofacial deformity leading to initiation of orthopaedic treatment. We found that initial radiological signs of dentofacial deformities were subtle and characterized by minor mandibular asymmetry and occlusal plane steepening. Radiological findings of TMJ deformity associated with initial dentofacial deformity were frequent and characterized by condylar articular surface flattening (OR 8.42), condylar subcortical cyst (OR 5.94), condylar surface erosion (OR 5.38) and condylar deviation in form (OR 25.39). Radiological signs of TMJ deformity were also documented in TMJs considered “healthy” during initial clinical and radiological examination. This study presents new knowledge of importance for early diagnosis of dentofacial deformity in JIA. Early diagnosis of dentofacial deformity is important as treatment outcome is greatly influenced by timely initiation.